Respuesta :

Set each expression from the parentheses equal to 0 separately like so:

Equation 1: x - 4 = 0

Equation 2: -5x + 1 = 0

Now for each equation solve for x!

Equation 1:

x +(- 4 + 4) = 0 + 4

x = 4

Equation 2:

-5x +( 1-1) = 0 - 1

-5x/ -5 = -1 / -5

x = 1/5

Check:

(4 - 4)(-5*4 + 1)

(0) (-20 + 1)

(0) (-19)

0 = 0 -------------------------> correct!

(1/5 - 4)(-5 * 1/5 + 1)

(-19/5)(-1 + 1)

(-19/5)(0)

0 = 0 -------------------------> correct!

smaller x = 1/5

larger x = 4

Hope this helped!

Answer:

smaller x = 1/5

larger x = 4

Step-by-step explanation:

ACCESS MORE